Storm-Induced Dynamics of Particulate Organic Carbon in Clear Creek, Iowa: An Intensively Managed Landscape Critical Zone Observatory Story - Kim, Jieun; Blair, Neal E.; Ward, Adam S.; Goff, Katie (Frontiers in Water, 2020)
Rivers integrate and transport particulate organic carbon (POC) from multiple sources with varied diagenetic histories. A significant amount of POC is delivered to rivers during storm events, but the sources and fates of the mobilized material are often unclear. To gauge the relative contributions of variability of different input sources, this study uses a biomarker approach that broadly characterizes organic matter on the molecular level. Suspended sediment was collected during a storm in October 2015 at three nested sampling locations along Clear Creek in Iowa, U.S.A. Supplemented with bulk elemental and C-isotopic measurements, biomarker analyses were obtained to identify changes in the sources and the diagenetic state of the POC. Fatty acid-rich organic matter was attributed to the mobilization of algal mats in the stream channel at the early stage of the storm as precipitation initiated and water velocities began to increase. A significant contribution of lignin-rich material occurred at peak precipitation and elevated discharge signifying erosion from row crop field surfaces and bank soil sources. Tracers of oxidized lignin and soil organic matter suggested that this was a partially time-resolved mixture of fresh and degraded material derived. Storm-induced variations of biomarkers were observed at the three sampling stations located throughout the watershed. The mixing patterns became more complex as the storm pulse moved downstream due to the additive contributions of multiple tributaries and the hypothesized increasing relative importance of alluvial bank erosion. The increase is attributed to a systematic transition in basin geomorphology from a V-shape in the upper reach to a wider box-shaped valley in the lower reach. Even though standing crop biomarker concentration measurements revealed a diversity of sources over time, the complex mixture of POC associated with peak discharge dominated the flux of material downstream. This study highlights the complexity of storm-initiated C-transport and the need for high spaciotemporal resolution broad spectrum tracer studies in the future.